2013
DOI: 10.1590/s1981-67232013005000014
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the use of potassium sorbate and sodium metabisulphite for the chemical and microbial stability of carbonated coconut water

Abstract: Coconut water is popular worldwide, mainly because of its pleasant sensory characteristics, nutritional value and low calorie density. However, coconut water is a highly perishable product due to the presence of enzymes such as peroxidase and polyphenoloxidase, which cause undesirable changes in colour, and also because of its susceptibility to microbial spoilage. The use of chemical additives has been adopted by the industry with the intent of increasing product shelf life. In this study, the efficiency of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 11 publications
(7 reference statements)
1
3
0
1
Order By: Relevance
“…Thus the treated sample stored at 4 0 C for Potassium sorbate showed a reduction in microbial population to that of the Sodium benzoate. The results of this study are in line with the results conducted by Pereira et al, (2013) [4] who preserved lime juice with Potassium sorbate preservative.…”
Section: Microbial Load In Fresh Tender and Processed Tender Coconut Watersupporting
confidence: 93%
“…Thus the treated sample stored at 4 0 C for Potassium sorbate showed a reduction in microbial population to that of the Sodium benzoate. The results of this study are in line with the results conducted by Pereira et al, (2013) [4] who preserved lime juice with Potassium sorbate preservative.…”
Section: Microbial Load In Fresh Tender and Processed Tender Coconut Watersupporting
confidence: 93%
“…---------considered as a model product to be investigated because despite the different studies that have been performed using different technologies (such as the conventional thermal process (Fontan et al,. 2012;Murasaki-Aliberti et al, 2009;Tan et al, 2014b), membranes (Das Purkayastha et al, 2012;Nakano et al, 2011) , use of additives (Abreu y Faria, 2007;Pereira et al, 2013), microwave (Matsui et al, 2007;Matsui et al, 2008) and ultraviolet radiation (Augusto et al, 2015), problems related with its enzyme stability (POD and PPO) are still observed.…”
Section: Universidad Nacional De Trujillomentioning
confidence: 99%
“…For storage time, the reference [44], evaluating the pH of the mixed beverage produced with green tea and apple also did not observe the storage influence. Regarding the use of preservatives, the reference [45] also reported high pH when used the potassium sorbate and sodium metabisulphite on the coconut water stability. These authors observed that the samples that did not receive preservative presented less stability.…”
Section: Storage Of the Mixed Nectar Of Cupuassu And Green Teamentioning
confidence: 99%